Identification of two novel cytolysins from the hydrozoan Olindias sambaquiensis (Cnidaria) - Haddad Junior, Vidal [UNESP]; Zara, Fernando [UNESP]; Marangoni, Sergio; Toyama, Daniela de Oliveira; Felizardo de Souza, Alex Jardelino [UNESP]; Buzzo de Oliveira, Simone Cristina [UNESP]; Toyama, Marcos Hikari [UNESP] (Biomed Central Ltd., 2014)
Background: Although the hydrozoan Olindias sambaquiensis is the most common jellyfish associated with human envenomation in southeastern and southern Brazil, information about the composition of its venom is rare. Thus, the present study aimed to analyze pharmacological aspects of O. sambaquiensis venom as well as clinical manifestations observed in affected patients. Crude protein extracts were prepared from the tentacles of animals; peptides and proteins were sequenced and submitted to circular dichroism spectroscopy. Creatine kinase, cytotoxicity and hemolytic activity were evaluated by specific methods.Results: We identified two novel cytolysins denominated oshem 1 and oshem 2 from the tentacles of this jellyfish. The cytolysins presented the amino acid sequences NEGKAKCGNTAGSKLTFKSADECTKTGQK (oshem 1) and NNSKAKCGDLAGWSKLTFKSADECTKTGQKS (oshem 2) with respective molecular masses of 3.013 kDa and 3.375 kDa. Circular dichroism revealed that oshem 1 has random coils and small a-helix conformation as main secondary structure whereas oshem 2 presents mainly random coils as its main secondary structure probably due to the presence of W (13) in oshem 2. The hemolysis levels induced by oshem 1 and oshem 2 using a peptide concentration of 0.2 mg/mL were, respectively, 51.7 +/- 6.5% and 32.9 +/- 8.7% (n = 12 and p <= 0.05). Oshem 1 and oshem 2 showed significant myonecrotic activity, evaluated by respective CK level measurements of 1890.4 +/- 89 and 1212.5 +/- 103 (n = 4 and p <= 0.05). In addition, myonecrosis was also evaluated by cell survival, which was measured at 72.4 +/- 8.6% and 83.5 +/- 6.7% (n = 12 and p <= 0.05), respectively. The structural analysis showed that both oshem 1 and oshem 2 should be classified as a small basic hemolytic peptide.Conclusion: The amino acid sequences of two peptides were highly similar while the primary amino acid sequence analysis revealed W (22th) as the most important mutation. Finally oshem 1 and oshem 2 are the first cytolytic peptides isolated from the Olindias sambaquiensis and should probably represent a novel class of cytolytic peptides.
Keywords: Olindias sambaquiensis; Hemolytic; Myonecrosis; Cytotoxicity; Cytolysin; Cnidaria venom